International Commodity Prices and Domestic Bank Lending in Developing Countries - Agrawal, Isha (IMF Working Papers; Working Paper ;, 2017)
We study the role of the bank-lending channel in propagating fluctuations in commodity prices to credit aggregates and economic activity in developing countries. We use data on more than 1,600 banks from 78 developing countries to analyze the transmission of changes in international commodity prices to domestic bank lending. Identification relies on a bankspecific time-varying measure of bank sensitivity to changes in commodity prices, based on daily data on bank stock prices. We find that a fall in commodity prices reduces bank lending, although this effect is confined to low-income countries and driven by commodity price busts. Banks with relatively lower deposits and poor asset quality transmit commodity price changes to lending more aggressively, supporting the hypothesis that the overall credit response to commodity prices works also through the credit supply channel. Our results also show that there is no significant difference in the behavior of foreign and domestic banks in the transmission process, reflecting the regional footprint of foreign banks in developing countries.